The Implication of Inquiry Learning Approach Toward Students’ Achievement in Biology of X Grade Students of SMA Negeri 2 Surakarta - Astri Setiawati; Alvi Rosyidi; Bowo Sugiyarto (Universitas Sebelas Maret, 2013)
This research aims are to find out: 1) the influence of inquiry approach toward student’s achievement in cognitive domain; 2) the influence of inquiry approach toward student’s achievement in affective domain; 3) the influence of inquiry approach toward student’s achievement in pshycomotor domain; 4) the best approach toward student’s achievement; and 5) the most effective approach toward student’s achievement of studying biology on X grade of SMA Negeri 2 Surakarta. This research is a quasi experiment research with randomized control only design using inquiry approach and conventional approach as independent variables and student’s achievement of study biology as the dependent variable. Here, it is acquired three classes as the samples, there are the student’s of class X-1 as the control class, student’s of class X-2 as the first experimental class, and student’s of class X-3 as the second experimental class. The population of this research is all of the student’s was X grade of SMA Negeri 2 Surakarta. The sample of this research was established by cluster random sampling. The techniques for collecting data are by using test, questionnaire, and documentation. The data were analyzed by anova and then by scheffe test. The conclusion of this research are: 1) There is an influence of inquiry approach toward student’s achievement in cognitive domain; 2) There is no influence of inquiry approach toward student’s achievement in affective domain; 3) There is an influence of inquiry approach toward student’s achievement in pshycomotor domain; 4) Modified free inquiry is the best approach to influence the student’s achievement based on cognitive domain, guided inquiry approach and modified free approach are better to influence the student’s achievement on pshycomotor domain; and 5) The most effective approach to influence the student’s achievement is modified free inquiry. Key Words: inquiry learning approach, achievement, Biology.